Palliative and end-of-life care in glioblastoma: defining and measuring opportunities to improve care - Hemminger, Lauryn E (Neurooncol Pract, 2017)
BACKGROUND: American Society for Clinical Oncology (ASCO) quality measures for terminal cancers recommend early advance care planning and hospice at the end of life. We sought to evaluate adherence to 5 palliative care quality measures and explore associations with patient outcomes in glioblastoma. METHODS: This is a retrospective analysis of 117 deceased glioblastoma patients over 5 years. Records were reviewed to describe adherence to palliative care quality measures and patient outcomes. Data regarding emotional assessments, advance directives, palliative care consultation, chemotherapy administration, hospice, location of death, and overall survival were collected. RESULTS: Median overall survival was 12.9 months. By the second oncology visit, 22.2% (26/117) had an emotional assessment completed. Advance directives were documented for 52.1% (61/117) by the third neuro-oncology visit (30/61 health care proxy), yet 26.5% (31/117) did not have any advance directive before the last month of life. With regard to other ASCO quality measures, 36.8% (43/117) had a palliative care consult; 94.0% (110/117) did not receive chemotherapy in the last 14 days of life; 59.8% (70/117) enrolled in hospice >7 days before death; and 56.4% (66/117) died in a home setting. Patients who enrolled in hospice >7 days before death were 3.56 times more likely to die in a home setting than patients enrolled <7 days before death or with no hospice enrollment (P = .002, [OR 3.56; 95% CI, 1.57–8.04]). CONCLUSIONS: Late advance directive documentation, minimal early palliative care involvement, and the association of early hospice enrollment with death in a home setting underscore the need to improve care and better define palliative care quality measures in glioblastoma.